Innovative substructuring technique for hybrid simulation of multistory buildings through collapse - Hashemi, M. Javad; Mosqueda, Gilberto (Earthquake engineering & structural dynamics, 2014)
SUMMARY Hybrid simulation combines numerical and experimental methods for cost‐effective, large‐scale testing of structures under simulated dynamic earthquake loads. Particularly for experimental seismic collapse simulation of structures, hybrid testing can be an attractive alternative to earthquake simulators due to the limited capacity of most facilities and the difficulties and risks associated with a collapsing structure on a shaking table. The benefits of hybrid simulation through collapse can be further enhanced through accurate and practical substructuring techniques that do not require testing the entire structure. An innovative substructuring technique for hybrid simulation of structures subjected to large deformations is proposed to simplify the boundary conditions by overlapping the domains between the numerical and experimental subassemblies. The advantages of this substructuring technique are the following: it requires only critical components of the structure to be tested experimentally; it reduces the number of actuators at the interface of the experimental subassemblies; and it can be implemented using typically available equipment in laboratories. Compared with previous overlapping methods that have been applied in hybrid simulation, this approach requires additional sensing in the hybrid simulation feedback loop to obtain internal member forces, but provides significantly better accuracy in the highly nonlinear range. The proposed substructuring technique is verified numerically and validated experimentally, using the response of a four‐story moment‐resisting frame that was previously tested to collapse on an earthquake simulator. Copyright © 2014 John Wiley & Sons, Ltd.